P-A9 Transformation of Darunavir into a long acting nanoformulated prodrug. (April 2018) - Banoub, Mary; Bade, Aditya; McMillan, JoEllyn; Edagwa, Benson; Gendelman, Howard
Abstract : Antiretroviral therapy (ART) has improved the quality and longevity of HIV-1 patients. Despite such advances limitations in drug bioavailability, resistance, and secondary toxicities abound affecting regimen adherence. We posit that such pharmaceutical limitations may be overcome by drug transformation into long acting slow effective release ART (LASER ART); a pharmaceutical approach that improves cell and tissue drug penetrance and depot formation leading to extended dosing intervals and improved antiretroviral responses. To this end, a hydrophobic bioreversible derivative prodrug of darunavir (DRV) was synthesized by medicinal chemistry. Modified DRV (MDRV) was synthesized by covalent linkage of a 14-carbon hydrophobic fatty acid moiety to the parent drug through a hemiaminal bond. A stable poloxamer 407 coated prodrug DRV nanoformulations (NMDRV) produced by high-pressure homogenization. Physicochemical properties of NMDRV and resultant particle cell uptake, antiretroviral efficacy pharmacokinetic and biodistribution studies were performed with subsequent comparisons made between prodrug and native drug formulations. Laboratory and pharmacokinetic tests were performed in monocyte derived macrophages (MDM) and BALB/c mice, respectively. NMDRV displayed up to 86 mg per 106 cells in 24 hours and retention up to 2 weeks compared to undetectable levels in the native DRV treatment. Effective plasma DRV concentration was detected in the prodrug arm through day 7 following a single dose of 40 mg/kg compared to undetectable levels in the parent drug treatment arm. The results highlight opportunities for LASER ART to achieve improved ART distribution and dissolution with limited toxicity for long-term HIV/AIDS treatments.